Odoo 10 development essentials. - Reis, Daniel (Software developer) (Packt Publishing, 2016)
About This BookGet the most up-to-date guide on Odoo 10 and learn how to build excellent business applications with OdooThis example-rich, easy-to-follow guide enables you to build apps appropriate to your business needsCreate solid business applications with the help of this precise, to-the-point guideWho This Book Is For This book caters to developers who are familiar with Python and MVC design and now want to build effective business applications using Odoo. What You Will LearnInstall Odoo from source code and use all the basic techniques to set up and manage your Odoo server instancesCreate your first Odoo applicationAdd Odoo's social and messaging features to your own modulesGet to know the essentials of models and viewsUnderstand and use the Server API to add business logicUse Qweb to create custom reportsExtend Odoo CMS features to create your own website controllers and pages Leverage Odoo workflows in your applicationsWrite module-automated tests and debugging techniquesDeploy your Odoo applications for production useIn Detail Odoo 10 Development Essentials will not only teach you how to build and customize business applications with Odoo, but it will also cover all the new features that Odoo has to offer. This book is the latest resource on developing and customizing Odoo 10 applications. It comes packed with much more and more refined content than its predecessor. It starts with building business applications from scratch and covers topics such as installation and building your first Odoo application. It moves on to cover topics such as module extensions for adding social and messaging features to your application. In addition to this, it covers how to serialize your data and create data modules out of that data. Following this, the book also covers the latest features of Odoo 10, in addition to front-end development, testing and.